Komunikasi dan Budaya - Hanix Ammaria (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2017)
Communication is the process of delivering messages from one person to another in order to influence one's knowledge or behavior. In communication there are also elements, including: source, message, media, recipient, influence, feedback, environment. While Culture is matters pertaining to the way of human life. Humans learn to think, feel, believe, and work out what is culturally appropriate. The languages of friendship, eating habits, communication practices, social actions, economic activities, politics and technology, are all based on cultural patterns. Communication and culture are not just two words but two concepts that can not be separated.